A comparison of GIS packages for geospatial data pre-processing - Ndanusa, Ahmed; Md Dahalin, Zulkhairi; Ta'a, Azman (2018)
This paper aims to assess the choice of geographic information systems (GIS) used in pre-process geospatial data sets.The study conducted a comparative review of some of the commonly used GIS packages with the aim of proposing the most reliable in terms of consistency, functionality, user-friendliness and cost-effectiveness, which are the determinants in adopting any GIS packages. By this systematic assessment, both the current and potential users will be able to take full advantage of the most efficient GIS package to perform various analytical pre-processing tasks.The outcome of the assessment could be adopted as a guide for selecting an appropriate and reliable open source GIS platform for a timely and efficient pre-preprocessing geospatial data for environmental analysis.